Subjective and objective levels of physical activity and their association with cardiorespiratory fitness in rheumatoid arthritis patients - Yu, C.; Rouse, P.; Veldhuijzen Van Zanten, J.; Ntoumanis, Nikos; Kitas, G.; Duda, J.; Metsios, G. (BioMed Central Ltd., 2015)
Introduction: The aims of the present study were: (a) to examine the agreement between subjective (assessed via the International Physical Activity Questionnaire; IPAQ) and objective (accelerometry; GT3X) physical activity (PA) levels in patients with rheumatoid arthritis (RA), and (b) to evaluate the associations of RA patients' subjective and objective PA to their scores on the maximal oxygen uptake test (VO2max). Methods: The participants wore the GT3X for seven days before completing the IPAQ and VO2max test. The Bland-Altman plot was used to illustrate the agreement between the objective and subjective PA data, and the Wilcoxon test was employed to examine the differences. The association between the PA measurement and VO2max test was examined via the correlations and the magnitude was presented by the Steiger's Z value. Results: Sixty-eight RA patients (age = 55 ± 13 years, body mass index: 27.8 ± 5.4 kg/m2, median of disease duration = 5 (2 8) yrs) were recruited. Smaller differences between the subjective and objective measures were found when PA was assessed at the moderate level. Wilcoxon tests revealed that patients reported less time spent engaged in sedentary behaviours (Z = -6.80, P< 0.01) and light PA (Z = -6.89, P < 0.01) and more moderate PA (Z = -6.26, P < 0.01) than was objectively indicated. Significant positive correlations were revealed between VO2max with all PA levels derived from accelerometry (light PA rho = .35, P < .01; moderate PA rho = .34, P = .01; moderate and vigorous PA, (MVPA) rho = .33, P = .01), and a negative association to sedentary time (ST) emerged (rho = -.27, P = .04). IPAQ-reported moderate PA and MVPA positively correlated with maxV02 (rho = .25, P = .01, rho = .27, P = .01, respectively). Differences between the magnitude of correlations between the IPAQ-VO2 max and GT3X-VO2 max were only significant for ST (Z = 3.43, P < .01). Conclusions: Via responses to the IPAQ, RA patients reported that they were less sedentary and engaged in more higher intensity PA than what was objectively assessed. Accelerometry data correlated with VO2max at all PA levels. Only subjective moderate and MPVA correlated with VO2max. Findings suggest that self-reported PA and ST should be interpreted with caution in people with RA and complemented with accelerometry when possible.